Pengaruh Ekstrak Jantung Pisang Kepok (musa paradisiac l) terhadap Penyembuhan Luka Perineum Derajat II pada Ibu Post Partum di Wilayah Kerja Puskesmas Gambesi Kota Ternate Tahun 2024 - Umaternate, Irawati; Hi. Saraha, Rosida (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
One of the solutions for postpartum mothers to accelerate the healing of perineal wounds in addition to using medical drugs is traditional medicine, which is obtained from the natural world, one of which is from banana plants to help accelerate the healing of postpartum mothers' perineal wounds, One of the plants that can be used as raw materials in the manufacture of modern medicines and traditional medicines is the banana plant (Musa paradisiaca Linn.). Kepok bananas have a very high antioxidant content and are signaled to be able to heal wounds. The purpose of this study was: to determine the effect of heart extract of banana kepok (Musa paradisiac L) on the healing of second-degree perineal wounds. The peer research type of Quasi experiment with the study method of one group pretest-posttest design, samples were taken by Accidental Sampling, as many as 45 people were pretested and posttest, with the Mann-Whitney and Wilcoxon test showing that the ρ value of the pretest-posttest from the treatment group with a dose of 100 gr/Kg/BB was 0.000 (<0.05), and the treatment group with a dose of 150 gr/Kg/BB was 0.000 (<0.05). So it can be concluded thatρ<α, so Ho was rejected and Ha was accepted, which means that there is an effect of kapok banana heart extract on the healing of second-degree perineal wounds. so it can be recommended for mothers with second-degree perineal injuries to consume kepok banana hearts as an alternative to accelerate healing.